Interactions of Pseudomonas aeruginosa with immunoglobulins and complement in sputum. - Hann, S (1976)
The interactions of Pseudomonas aeruginosa with humoral factors in the sputum of patients with cystic fibrosis were investigated by using an indirect immunofluorescent technique. Fluorescein-conjugated, monovalent antiserum specific to heavy chains of human immunoglobulin A (IgA), IgG, or IgM and to complement C3 were used. All strains of P. aeruginosa recovered from the sputum specimens of patients with cystic fibrosis were found to be coated with antibodies of IgA, IgG, and IgM classes and with C3. The specificity of the antibody coating was determined. The fluorescence was most intense with IgA and was followed in intensity by IgG, IgM, and C3. No difference was noted between rough and mucoid strains of P. aeruginosa. When the subcultured P. aeruginosa was incubated with the sputum eluates, a similar pattern of fluorescence was demonstrated, indicating that these humoral factors are present in the sputum and that the coating process can take place in the lower respiratory tract of the patients. By single radial immunodiffusion, significant quantities of the humoral factors in the sputum eluates were detected. These findings suggest that P. aeruginosa is opsonized in sputum of patients with cystic fibrosis.